Differences in the developmental origins of the periosteum may influence bone healing. (16th September 2014) - Ichikawa, Y.; Watahiki, J.; Nampo, T.; Nose, K.; Yamamoto, G.; Irie, T.; Mishima, K.; Maki, K.
<x xml:space="preserve">Abstract</x> Background and Objective The jaw bone, unlike most other bones, is derived from neural crest stem cells, so we hypothesized that it may have different characteristics to bones from other parts of the body, especially in the nature of its periosteum. The periosteum exhibits osteogenic potential and has received considerable attention as a grafting material for the repair of bone and joint defects. Material and Methods Gene expression profiles of jaw bone and periosteum were evaluated by DNA microarray and real‐time polymerase chain reaction. Furthermore, we perforated an area 2 mm in diameter on mouse frontal and parietal bones. Bone regeneration of these calvarial defects was evaluated using microcomputed tomography and histological analysis. Results The DNA microarray data revealed close homology between the gene expression profiles within the ilium and femur. The gene expression of Wnt‐1, SOX10, nestin, and musashi‐1 were significantly higher in the jaw bone than in other locations. Microcomputed tomography and histological analysis revealed that the jaw bone had superior bone regenerative abilities than other bones. Conclusion Jaw bone periosteum exhibits a unique gene expression profile that is associated with neural crest cells and has a positive influence on bone regeneration when used as a graft material to repair bone defects. A full investigation of the biological and mechanical properties of jaw bone as an alternative graft material for jaw reconstructive surgery is recommended.